Pengaruh Kinerja Sosial Terhadap Profitabilitas Bank Syariah - Puspasari, Rosana; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aimed to investigate the effect of social performance to the profitability of sharia bank. This study uses quantitative approach with multiple regression analysis and four variables; they are Mudharabah-Musyarakah Financing, Qardh Financing, and Zakat as exogenous variables and Net income as endogenous variable.Based on findings, it revealed that Mudharabah-Musyarakah Financing and Zakat effect significantly positive to the net income of Sharia commercial bank. Meanwhile Qardh Financing has non-significantly effect to the net income of Sharia commercial bank. On the other hand, Musyarakah-Mudharabah financing, Qardh financing and Zakat simultaneously has significantly effect to the net income of Sharia commercial bank.